2019
DOI: 10.3390/cancers11121901
|View full text |Cite
|
Sign up to set email alerts
|

Parallel Structure Deep Neural Network Using CNN and RNN with an Attention Mechanism for Breast Cancer Histology Image Classification

Abstract: In this paper, we present a new deep learning model to classify hematoxylin–eosin-stained breast biopsy images into four classes (normal tissues, benign lesions, in situ carcinomas, and invasive carcinomas). Our model uses a parallel structure consist of a convolutional neural network (CNN) and a recurrent neural network (RNN) for image feature extraction, which is greatly different from the common existed serial method of extracting image features by CNN and then inputting them into RNN. Then, we introduce a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
57
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 102 publications
(57 citation statements)
references
References 28 publications
0
57
0
Order By: Relevance
“…In this way, 675 images were used for training whereas the remaining 170 images were kept for testing the model. Following [35], we used 5-fold cross-validation on training images which means that 540 images were used for training and 135 images for validation purpose. Again, we have an equal percentage of non-carcinoma and carcinoma images in training and validation.…”
Section: Training Criteriamentioning
confidence: 99%
“…In this way, 675 images were used for training whereas the remaining 170 images were kept for testing the model. Following [35], we used 5-fold cross-validation on training images which means that 540 images were used for training and 135 images for validation purpose. Again, we have an equal percentage of non-carcinoma and carcinoma images in training and validation.…”
Section: Training Criteriamentioning
confidence: 99%
“…This consists of a range of activities such as the acquisition, storage, sharing, analysis and interpretation of histological images [ 10 ]. In this domain, computer-assisted classification of tissue samples has attracted considerable research interest in recent years as a means for assisting pathologists in several tasks, for instance, the classification of specimens into normal or abnormal [ 11 , 12 , 13 , 14 ], the grading of neoplastic tissue [ 15 , 16 , 17 , 18 ], the estimation of tumor proliferation [ 19 ] and the identification of tissue substructures such as epithelium, stroma, lymphocytes, necrosis, etc. [ 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Most recently, RNNs have shown excellent results in the classification of histopathological images. Yao et al 21 demonstrated superior results with a parallel system of CNN and RNN in the image classification of four classes of breast biopsy histopathology images (normal breast tissue, benign, carcinoma in situ, and invasive carcinoma) compared to CNN alone. Iizuka et al 22 used a combined CNN and RNN on WSIs of stomach and colon biopsies.…”
Section: Discussionmentioning
confidence: 99%